Analysis of Village Residents Receiving Social Assistance Using Linear Regression Method - Rafli Fitriawan; Saragih, Rusmin; Ambarita, Indah (Yayasan Kita Menulis, 2024)
This study aims to analyze the recipients of social assistance in Banyumas Village using the simple linear regression method. The research examines how household income affects the amount of social assistance received. Data was collected from the Banyumas Village Office, including information on income and the amount of social assistance received by residents. The results show a negative relationship between household income and the amount of assistance received, where higher income leads to smaller assistance. The model also demonstrates good accuracy with an average prediction error (MAPE) of 9.38%. Additionally, an R² value of 0.999972 indicates that the model can explain almost all variations in the data. This study provides valuable insights into the effectiveness of the social assistance program in Banyumas Village and to help improve the program in the future.